Autonomy characterization as a key indicator of learning-to-learn skills in medical students - Yolanda Cabrera Macìas; Annia Esther Vizcaíno Escobar; José Aurelio Díaz Quiñones; Ernesto José López González; Ernesto López Cabrera (Medisur)
Background: autonomy allows students to think for themselves, critically and independently, take into account different points of view and act accordingly. It constitutes a necessary indicator in the study of learning-to-learn skills. Objective: to characterize autonomy as an indicator of learning-to-learn skills in medical students. Methods: a mixed research design of the sequential explanatory type was used. The research was carried out from October 2021 to March 2022 at the Cienfuegos University of Medical Sciences. The intentional, non-probabilistic sample was made up of 255 Medicine first-year students. The questionnaire that evaluates the learning to learn skills training level, observations of teaching activities and focus groups were used to collect information. Results: autonomy is present in 45.4% of the students, according to the questionnaire. In the focus groups, some students acknowledge presenting deficiencies in some autonomy indicators, which corresponds to the data obtained in the observations of teaching activities. Conclusions: autonomy as a learning to learn skills key indicator in the Cienfuegos Medical Sciences University first-year students, was characterized by a low expression in the medical students’ learning processes.